2022
DOI: 10.1088/1742-6596/2190/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure plasma jet for surface material modification: a mini-review

Abstract: Plasma jet is one of the methods for surface material modification that is economically and environmentally friendly. This method can be applied in ambient pressure that makes this method more feasible. The discharge of plasma from the plasma jet can be adjusted according to the design used. Carrier gas that is used in the plasma jet system can also be adapted to the needs or appropriate to the target material. The gases that can be used are helium, argon, etc. A variant gas flow rate will also affect the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cold plasma jets, particularly atmospheric pressure cold plasma jets (APCPJs) excited by pulsed power supplies, operate at low gas temperatures and contain an abundance of excited state particles, ultraviolet photons, ozone molecules, free radicals, etc. They hold significant potential for a wide range of applications, including surface modification, disinfection and sterilization, air purification, wastewater treatment, and others [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Cold plasma jets, particularly atmospheric pressure cold plasma jets (APCPJs) excited by pulsed power supplies, operate at low gas temperatures and contain an abundance of excited state particles, ultraviolet photons, ozone molecules, free radicals, etc. They hold significant potential for a wide range of applications, including surface modification, disinfection and sterilization, air purification, wastewater treatment, and others [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure discharge plasma has been widely used in many applications, such as biomedicine [16], material modification [17,18], soil remediation [19,20], directional transport of droplets [21] and artificial precipitation [22]. As a significant branch of the field, electrostatic fog harvesting has been extensively studied over the last 50 years worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of various material surfaces with NTP have been investigated 21 24 , but most often aimed at specific changes in surface properties rather than addressing potential material damage. Setiawan et al 21 reported a mini-review describing the plasma jet-produced NTP treatment of different materials (e.g., polymers, stainless steel, carbon material) and concluded that this treatment modifies the surface of the materials with the desired functional groups, changes its wettability, but does not change the properties within the material. Alavi et al 25 demonstrated that an atmospheric pressure plasma jet can locally activate the surfaces of 3D-printed structural polymers for the reagent-free covalent attachment of proteins and hydrogel.…”
Section: Introductionmentioning
confidence: 99%